Prevalence of syphilis and associated factors among pregnant women in Brazil: systematic review and meta-analysis - Iana Mundim de Oliveira; Regilane Cordeiro dos Santos; Renan Alves Silva; Rosane Ribeiro Figueiredo Alves; Bruno César Teodoro Martins; Leonardo Ribeiro Soares (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2024)
Abstract Objective: This systematic review accompanied by a meta-analysis aimed to estimate the prevalence of syphilis in pregnant women in Brazil and describe its associated factors. Methods: Following the establishment the search strategies and the registration of the review protocol in PROSPERO, we conducted a search for relevant articles in the Pubmed, LILACS, Science Direct, SciELO and Web of Science databases. Our inclusion criteria were cross-sectional studies published between 2005 and 2023, with no language restrictions. The combined prevalence of syphilis infection was estimated using the random effects model in the R Software with a 95% confidence interval (95% CI) and p < 0.01 as statistically significant. Results: A total of 24 articles were recruited, which together investigated 221,884 women. The combined prevalence of syphilis in pregnant women in Brazil was 1.79% (95% CI: 1.24-2.57%), and the main factors associated with its occurrence were black and brown skin color, low education and factors related to the partner. Conclusion: There was a high prevalence of syphilis in pregnancy in Brazil, mainly associated with socioeconomic factors.